Sintaxonomic concerns on Genista polyanthos R. Roem. ex Willk. broomlands - Vila-Viçosa, Carlos (2014)
As result of several field trips following PhD researches in Marianic-Monchiquensean Sector, we describe a new broomland association named Genistetum triachanthi-polyanthi as a thermomediterranean, oceanic and sub-humid to humid, schistose association. The 26 relevés analysis, combining phytosociologic methodology with hierarchical cluster analysis (Ward's Hierarchical Clustering, based on Bray-Curtis distance) allowed the segregation of this Monchiquense association. Appearing as a regressive stage, or fringe, of secondary or edaphoxerophilous cork oak and, punctually, holm oak woodlands, it reveals a high sinecological value, in a wide variety of edaphoclimatic typologies, despite its poorest species number, since it includes restrict distribution taxa with high conservational value. At last, sintaxonomic issues are highlighted as these hyperxerophilous broomlands detach themselves easily from main Cytisetea scopario-striati diagnosis, being intermixed in contrasting ecological diagnosis, with major frequency of Calluno vulgaris-Ulicetea minoris elements, under extremely different edaphoclimatic envelopes, different landscapes and serial dynamics.